ANALISIS POTENSI KONVERGENSI EKONOMI NEGARA ANGGOTA ASEAN-10 TAHUN 2015-2021 DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Holifah, Husnul; Togar Laut, Lorentino; Sugiharti, Rr. Retno (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2024)
In 2015 is the year of the acceleration of the establishment of the ASEAN Economic Community (AEC), therefore it is necessary to analyze the economy of each member country based on factors that affect the convergence process. This study aims to analyze the level of convergence of economic growth among ASEAN-10 member countries in 2015-2021. The data used is secondary data obtained from the world bank website. The analytical methods used in this study are sigma convergence and beta convergence. The calculation of sigma convergence uses mathematical analysis of the coefficient of variation of GDP per capita of ASEAN-10 member countries. While the calculation of beta convergence uses panel data regression analysis with a fixed effect model approach. The results showed that there was no sigma convergence among ASEAN-10 member countries, indicating that there was no decrease in inequality among member countries. The results of the analysis on beta convergence show that there is absolute and conditional beta convergence at a rate of 7,5% and 3,1%. It was found that the Foreign Direct Investment and Total Labor Force variables did not have a significant effect, while the Trade Openness variable had a significant effect.